Posttraumatic Stress and Sleep: Differential Relations across Types of Symptoms and Sleep Problems - Babson, Kimberly (2011)
Posttraumatic stress symptoms and self-reported sleep problems reliably covary. The current study investigated how posttraumatic stress symptom clusters (i.e., hyperarousal, avoidance, and reexperiencing) relate to trouble initiating and maintaining sleep and nightmares. Participants included traumatic event-exposed respondents from the NCS-R. Results suggested that posttraumatic stress symptom severity is related to trouble initiating and maintaining sleep and nightmares. Investigation of symptom clusters indicated that reexperiencing symptoms were related to trouble initiating and maintaining sleep and nightmares, while hyperarousal symptoms were related to trouble maintaining sleep and nightmares. Findings partially support both reexperiencing and hyperarousal-based models of the relation between sleep and posttraumatic stress.